Narasi Sejarah Novel Tambora Karya Agus Sumbogo: Kajian Sosiologi Sastra - Mulyadi, Ardini; Jelantik SP, Ida Bagus (Humanis; Vol 22 No 1 (2018)DO - 10.24843/JH.2018.v22.i01.p11, 2018)
The data of this study were taken from an Indonesia novel entitled ‘ Tambora ’ by Agus Sumbogo (2015) as a research objective caused some factors. First, ‘ Tambora ’ novel telling us the beginning of Lesley journey to return the precious things of Tambora’s people. Second, ‘ Tambora ’ novel describe the story and phenomena that exist before Mount Tambora was erupted. Third, ‘ Tambora ’ novel related to the destruction of the third sultanate people that is located close around Mount Tambora caused by Dutch confront Devide et Impera. The writer have analyzed the problems in the novel, such as structures, history, and social aspect of the third sulatanate which exist in Tambora area. The theory used in this study was structural theory applied to analyze the characters, especially the element of characterization, plot, and setting. Moreover, this study also presented the history revealed before Mount Tambora was erupted. The writer also uses the sociology of literature theory taken from the book by Burhan Nurgiyantoro 2005. The method used in collecting the data was literature review method with continuation technique in form of note taking technique. Afterwards, the method used in this research is descriptive analysis to describe the result related to the data that have been analyzed. Characterization in this novel can be divided into two, major character and additional characters. The major character in ‘ Tambora ’ novel named Lesley and additional characters are Uma, Jeff, and Wayan. The plot can be divided into three, they were beginning, middle, and an end. The plot used in Tambora novel is mixing plot. Afterward, the setting is divided into three, place, time, and social of story. This study also illustrates the history of the eruption of Mount Tambora either in fact or fiction. Based on sociology of literature theory, there are found some aspcets revealed in the Tambora novel , that is good and bad moral aspects, political aspect Devide et Impera, economic aspects of Tambora people,  social aspect of the good and bad sultanates relations, and cultural aspect to do the tradition that almost extinguished.